Mengamati Perkembangan Teknologi dan Bisnis Digital dalam Transisi Menuju Era Industri 5.0 - Vera Maria; Sherla Dara Rizky; Aisar Muhammad Akram (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Era 5.0 marks a societal shift towards deeper integration between humans and advanced technologies such as Artificial Intelligence (AI), Internet of Things (IoT), Big Data, and cloud computing. This article investigates recent developments in digital technology supporting Era 5.0, its impact on the business world, case studies of technology implementation, and challenges faced in transitioning towards this more connected era. Technologies like AI have transformed business operations by enhancing efficiency, personalizing services, and enabling more precise decision-making. Case studies from various sectors such as automotive, healthcare, and agriculture illustrate how companies adopt and integrate Era 5.0 technologies to create added value and maintain competitiveness. Despite the immense potential of Era 5.0, challenges such as data security, implementation costs, and organizational adaptation remain key focal points in executing this transformation. By considering these factors, the article underscores the importance of cross-sector collaboration, investment in skilled human resources, and awareness of ethical considerations in addressing challenges towards a more technologically connected society.